Constitution and Taxing Power - Medrano Cornejo, Humberto (1981)
This paper presents an approach to the new tax reforms that have emerged as a result of the Peruvian Political Constitution of 1979. The main objective is to identify the principles that the Constitution contains as a guarantee for taxpayers, and which in turn act as limits to the taxing power exercised by the State. This study provides an overview of the principles of legality, universality, obligatory nature, certainty and non-confiscatory nature of taxation, among others. In this respect, the author determines what the essential characteristics of tax law should be in order to regulate the power of the State and safeguard the interests of society.